2000
DOI: 10.31899/pgy6.1038
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent pregnancy and parenthood in South Africa

Abstract: The authors are thankful for the comments of Cynthia B. Lloyd and Lutske Newton. They also gratefully acknowledge the generous support of USAID Cooperative Agreement No.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 11 publications
3
63
0
Order By: Relevance
“…Participants reported that it may be more acceptable for women to tell their male partners that condoms should be used to prevent pregnancy rather than HIV, as pregnancy prevention has become more normative among South African youth due to the desire to complete higher education (Kaufman, DeWet and Stadler 2001). …”
Section: Resultsmentioning
confidence: 99%
“…Participants reported that it may be more acceptable for women to tell their male partners that condoms should be used to prevent pregnancy rather than HIV, as pregnancy prevention has become more normative among South African youth due to the desire to complete higher education (Kaufman, DeWet and Stadler 2001). …”
Section: Resultsmentioning
confidence: 99%
“…This differs from many other African countries. Kaufman et al (2001) found that many South African girls return to complete their schooling after giving birth and that this is a function of support from the girl's family and paternal recognition of the child. In a recent study in rural South Africa, Madhavan and Thomas (2005) confirm that childbearing impedes school enrollment and schooling, but young mothers can succeed in their educational careers if provided with flexible child care options.…”
Section: Interconnections Between Sexual Debut Teen Pregnancy and Smentioning
confidence: 99%
“…These participants argued that women should protect themselves and justified this by stating that men do not like condoms. This ties in to research which found that attitudes to condom use in South Africa are negative and linked to notions of masculinity and male pleasure (Kaufman et al 2001, Shisana et al 2014. By drawing on this type of discourse, these participants were able to construct themselves as aware of the risks of HIV and unplanned pregnancy and responsible in terms of regular testing.…”
Section: Conclusion: Linking Risk To Responsibilitymentioning
confidence: 82%